2010
DOI: 10.1007/s00787-009-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Total serum cholesterol levels and suicide attempts in child and adolescent psychiatric inpatients

Abstract: Associations between cholesterol and suicidal behavior in adolescent patients have not been explored in depth. In this study, 66 patients consecutively admitted to a psychiatric inpatient unit following attempted suicide were compared with a control group of 54 patients with no history of suicide attempts. The age range of the sample was from 8 to 18 years old. Cholesterol levels were significantly lower in attempted suicide patients than in controls (p \ 0.02), supporting the hypothesis that lower cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…1). Finally, a total of 65 studies met the inclusion criteria and were included in the meta-analysis: 8 cohort studies, 16,[26][27][28][29][30][31][32] 8 case-control studies 13,17,[33][34][35][36][37][38] and 49 cross-sectional studies, 9,10,14,15,18,19, involving 510 392 participants. The participants were categorized as follows: 1) patients with various psychiatric diseases (e.g., depression, schizophrenia, personality disorder, drug and alcohol addictions) with suicidality, who we defined as suicidal patients; 2) patients with various psychiatric diseases without suicidality, who we defined as nonsuicidal patients; and 3) healthy participants without any psychiatric disease and suicidality, who we defined as healthy controls.…”
Section: Search Resultsmentioning
confidence: 99%
“…1). Finally, a total of 65 studies met the inclusion criteria and were included in the meta-analysis: 8 cohort studies, 16,[26][27][28][29][30][31][32] 8 case-control studies 13,17,[33][34][35][36][37][38] and 49 cross-sectional studies, 9,10,14,15,18,19, involving 510 392 participants. The participants were categorized as follows: 1) patients with various psychiatric diseases (e.g., depression, schizophrenia, personality disorder, drug and alcohol addictions) with suicidality, who we defined as suicidal patients; 2) patients with various psychiatric diseases without suicidality, who we defined as nonsuicidal patients; and 3) healthy participants without any psychiatric disease and suicidality, who we defined as healthy controls.…”
Section: Search Resultsmentioning
confidence: 99%
“…In a study of 66 patients ranging from 8 to 18 years consecutively admitted to a psychiatric inpatient unit following attempted suicide, levels of cholesterol were found to be significantly lower in attempted suicide patients than in inpatients who had not attempted suicide. Control subjects were paired with case subjects according to psychiatric diagnosis, age and gender (Plana et al, 2010). In contrast, in a similar study of 152 adolescent psychiatric inpatients ranging from 12 to 21 years it was found that serum cholesterol levels were significantly higher in both male and female suicidal adolescent patients than in nonsuicidal adolescents.…”
Section: Introductionmentioning
confidence: 90%
“…Three metabolic studies investigated the relationship between suicide and self-harm behaviours and cholesterol. Lower total cholesterol levels were associated with a suicide attempt history [ 137 ], and increased severity of suicidal behaviour (e.g. ideations, gestures) among those who were currently suicidal [ 138 ], while lower high density lipid cholesterol was associated with higher suicide ideation [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“… FH+: ↑ peripheral and central BP, arterial stiffness and ↓ insulin sensitivity HC: 19.1 ± 0.1 HC (27M; 42F) Suicide and self-harm [ 138 ] SUC: 15.93 ± 1.48 SUC (15M; 32F) Examine the relationship between serum cholesterol levels and suicidal behaviours Metabolic: blood serum samples SUC: ↑ cholesterol ~ current suicide behaviour (within the SUC group, ↑ serum cholesterol ~ ↓ severity of SUC, but not ~ symptom severity) PC: 16.22 ± 1.95 PC (58M; 47F) Functional: SPI PD: 25.3 ± 3.3 PD (37M; 35F) Elucidate the relationships between alexithymia, suicide ideation and serum lipid levels. Metabolic: BMI, blood serum samples PD: ↓ HDL-C and ↑ VLDL-C ~ higher suicide ideation Functional: SSI [ 137 ] SA: 15.44 ± 1.99 SA (17M; 49F) Explore the associations between cholesterol and suicidal behaviour Metabolic: blood serum samples SA: ↓ cholesterol levels ~ attempted suicide history PC: 15.19 ± 1.68 PC (15M; 39F) Functional: hospital records [ 199 ] SA: 16.8 SEM = .74 SA (3M; 6F) Investigate platelet PBR density in suicidal teens Metabolic: blood serum samples SA: ↓ platelet PBR density PC: 16.5 SEM = .5 PC (7M; 3F) Functional: hospital records, SPI, SRS [ 155 ] SA: 15.87 ± 1.56 SA(10M; 25F) Evaluate the relationship between plasma serotonin levels and psychometric measures in suicidal adolescents Metabolic: blood serum samples SA: ↓ plasma 5-HT level ~ ↑ suicidality. (5-HT did not discriminate between the psychiatric diagnostic categories) PC: 16.29 1.81 PC (19M; 11F) Functional: hospital records, SPI ER: 16.91 2.47 ER (13M; 38F) HC: 15.26 1.41 HC (45M; 50F) ...…”
Section: Methodsmentioning
confidence: 99%